221k views
0 votes
Graph the following equation by plotting two points.y + 4 = -3(x - 6)

Graph the following equation by plotting two points.y + 4 = -3(x - 6)-example-1
User Mrana
by
5.2k points

1 Answer

2 votes

Step-by-step explanation

Step 1

isolate y


\begin{gathered} y+4=-3(x-6) \\ \text{break the parenthesis} \\ y+4=-3x+18 \\ \text{subtrac 4 in both sides} \\ y+4-4=-3x+18-4 \\ y=-3x+14 \end{gathered}

Step 2

now, we need 2 points or coordinates from the line, to do that we need

input a value for x to obtain the y value, so

a) when x= 4

replace in the equation and calculate}


\begin{gathered} y=-3x+14 \\ y=-3(4)+14 \\ y=-12+14 \\ y=2 \\ so,\text{ the coordinate is ( 4,2)} \end{gathered}

P1(4,2)

b)when x= 6


\begin{gathered} y=-3x+14 \\ y=-3(6)+14 \\ y=-18+14 \\ y=-4 \\ so,\text{ the coordinate is ( 6,-4)} \end{gathered}

P2(6,-4)

Step 3

finally, draw a line that passes through point P1 and P2

I hope this helps you

Graph the following equation by plotting two points.y + 4 = -3(x - 6)-example-1
User Armand Grillet
by
5.3k points